Логоси у вченні св. Максима Ісповідника як епістемологічні принципи стосунку Бога з людиною і світом - Hupalo, Mariia (Vox Patrum, 2018)
The knowledge of God and mystical union with Him is intimately connected with the concept of divine transcendence and immanence, His complete hiddenness, unknowability and, at the same time, his participatedness, grace and economical coming-out toward creature. Interrelatedness of these lies at the core of St. Maximus the Confessor’s concept of logoi. In this article we focus on how the principles of creation and participation of creature in God function as epistemological principles, according to which man can contemplate God in creatures and then move forward to direct contemplation and deifying participation in God. Special attention is paid to understanding logoi as an activity of God’s essence ad extra toward the created otherness. This activity brings existence, sense and identity to created beings and thus can be not only participated, but also known through natural contemplation.